The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4238/2015.june.26.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cytotoxicity induced by the anesthetic isoflurane: the role of inositol 1,4,5-trisphosphate receptors

Abstract: ABSTRACT. Isoflurane can induce widespread cytotoxicity. We hypothesized that isoflurane induces apoptosis partly by causing excessive calcium release from the endoplasmic reticulum (ER) via direct activation of inositol 1,4,5-trisphosphate receptors (IP 3 R). Rat pheochromocytoma cells cultured for seven days with nerve growth factor were divided into four groups: control group (C), IP 3 R antagonist group (X), isoflurane group (I) and isoflurane + IP 3 R antagonist group (I+X). Groups I and I+X were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It has been shown that brain development of rats at E21 is equivalent to that of human fetus at the gestational age of 12–16 weeks the second trimester [ 10 , 11 ]. In this study, pregnant SD rats at E21 were exposed to isoflurane to mimic anesthesia on pregnant woman in the second trimester; isoflurane at 1.3% and 2.0% is equivalent to 1 and 1.5 MAC, respectively [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that brain development of rats at E21 is equivalent to that of human fetus at the gestational age of 12–16 weeks the second trimester [ 10 , 11 ]. In this study, pregnant SD rats at E21 were exposed to isoflurane to mimic anesthesia on pregnant woman in the second trimester; isoflurane at 1.3% and 2.0% is equivalent to 1 and 1.5 MAC, respectively [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of anesthetic effects on the ER have focused on its role in modulating cell viability ( Q.J. Wang et al, 2008 ; Zhai et al, 2015 ; Liu et al, 2016 ). Our studies are the first to analyze the functional impact of anesthetic effects on ER Ca 2+ on neuronal function in intact hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In the nervous system of adult rats, isoflurane exposure for 1 MAC for 12 hours induced cytoxicity increased IP3R gene expression, and inhibition of IP3R activity did not completely block isoflurane-induced upregulation of IP3R mRNA expression, which was also associated with greater and faster elevation of peak (Ca2+). Sevoflurane and desflurane at equivalent exposure to isoflurane did not induce similar cytotoxicity or elevation of peak (Ca2+) [104,113] In conclusion isoflurane and sevoflurane induce cytotoxicity in the nervous system, which has significant adverse effects on neonatal and postnatal stage. In the adult effects nervous system result in increased vulnerability to cell damage.…”
Section: Role Of the Use Of Inhaled Anesthetics In Protection Againstmentioning
confidence: 97%
“…The differing effects of both anesthetics on the immature and mature nervous system have been investigated in recent years using in vitro Table 1 and in vivo murine models Table 2. The dates indicate that isoflurane and sevoflurane can inhibit NMDA receptor responses; these results suggest that both anesthetics might also be able to reduce or increase cytotoxic effects produced by excessive NMDA receptor stimulation, especially in the developing nervous system [102][103][104][105][106] In the nervous system of the developing rat, the deleterious effects of volatile anesthetics have demonstrated their greatest potential for harm between PD 0 -PD 14 [29,30,[107][108][109] Studies have determined the presence of apoptosis in the developing nervous system, as measured by expression of activated caspase-3 (CASP-3) and increases induced by the expression in proteins of cleaved CASP-3, for both isoflurane and sevoflurane [29,30,108,109].…”
Section: Role Of the Use Of Inhaled Anesthetics In Protection Againstmentioning
confidence: 97%